Micropropagação, teor e constituição química do óleo essencial de gerânio (Pelargonium graveolens L.) - Almeida, Sílvia Ávila de (2009)
A lot of vegetable species synthesize and accumulate organic substances, such as essential oils, that can be turned in alternative income for rural producers. Pelargonium graveolens L. is a native aromatic species from South Africa, commonly known as geranium. Its essential oil is largely used in perfume, cosmetics and fragrances industries, besides the aromatherapy. The conventional vegetative propagation methods of geranium do not present considerable success, which difficult the production of transplants in large scale. This way it is important to look for alternative production techniques, such as micropropagation, for this commercially important species. The aims of this work were to establish a protocol for micropopagation and acclimatization of geranium, besides investigating of essential oil content and chemical composition. The completely randomized design was used. For the micropropagation assays were tested different concentrations and immersion times of sodium hypochlorite and mercury chloride, different types of explants and MS salts concentrations, besides testing different concentrations of the plant growth regulators BAP, NAA, kinetin and IAA at presence and absence of light. For the acclimatization assay different substrates were tested. To analyze the essential oil we use plants propagated by rooting of cuttings and by micropropagation. Sodium hypochlorite at 1.2% for 12 minutes can be used for disinfestation of geranium explants, as well as mercury chloride at 0.09 and 0.08% for 12 and 14 minutes, respectively. The leaf explant is more effective for geranium micropropagation using MS medium with 39.8% of its salts. BAP and IAA proportionate the best results for in vitro multiplication and regeneration and number of shoots per explant. For acclimatization the substrates vermiculite and weekly addition of solution with salts of MS medium, coconut dust + Biosafra® (3-12-6) (12 g.L-1) + lime stone (1 g.L-1) and coconut dust + Biosafra® (3-12-6) (12 g.L-1) + lime stone (1 g.L-1) + vermiculite (1:1) can be used. There is a difference in geranium essential oil content and chemical composition between plants obtained from rooted cuttings and micropropagation.